Evaluation of Childhood Health Assessment Questionnaire in Juvenile Idiopathic Arthritis: A Single Center Experience From Turkey - Duygu GÜMÜŞ,; Özge BAŞARAN,; Nilgün ÇAKAR,; Nermin UNCU,; Banu ÇELİKEL ACAR, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the relationship between the Childhood Health Assessment Questionnaire (CHAQ) and types of juvenile idiopathic arthritis (JIA), the disease activity, laboratory findings, and treatments of patients with JIA. Patients and methods: Eighty-two children with JIA (37 males, 45 females; mean age 13.96±4.45 years) and 68 healthy children (31 males, 37 females; mean age 10.1±4.24 years) participated in the study. CHAQ, composed of discomfort and disability indexes, was applied to patients and the control group. Results: CHAQ score was significantly higher in JIA patients than in the control group (p<0.05). Patients having active joint involvement had significantly higher visual analog scale and CHAQ scores than those without active joint involvement (p<0.05). There were no statistical differences between the disease types and CHAQ scores (p>0.05). Visual analog scale pain scores and CHAQ scores were significantly higher in patients in an active disease period than patients in remission (p<0.05). Conclusion: The CHAQ is a reliable method for JIA follow-up. CHAQ clinically discriminates between healthy groups and JIA patients with a high disability index.